Desain Sanggul Pengantin Batak Toba Modifikasi Dengan Teknik Serat Nanas Modern - Titin Supiani; Sinta Alfalah (Universitas Negeri Jakarta, 2022)
The arrangement of the bridal bun continues to grow and many are created in the form of bun modifications, including the Toba Batak wedding bun. The purpose of this final project is to produce 3 Toba Batak bridal bun designs for several Batak traditional wedding ceremonies such as martumpol, traditional parties and mahursip where the bun is modified with modern pineapple fiber techniques and see the best results based on the jury's assessment. The assessment includes aspects of the theme of the bun design, the shape of the bun, the smoothness of the fiber of the bun, accessories, the neatness of the bun, the robustness of the bun. The assessment stage was carried out by 3 panelists, namely 2 makeup lecturers and 1 hairstylist. In the results of the overall assessment of the Batak Toba bridal bun design modified with modern pineapple fiber techniques, design 1 has a value of 82.6, design 2 has a value of 82.1, design 3 has the highest value of 83.98, it can be concluded that the best innovation of the three designs which is made is design 3. So it can be concluded that the overall display of the work is very good. Based on these results, it can be said that the experimental results can be used as a reference for implementing new innovations that follow the current trend, so that students and the general public are able to increase their interest and creativity in developing their work. Keywords: Modification, Design, Fiber Engineering